Fast and selective method for biogenic amines determination in wines and beers by ultra high-performance liquid chromatography. (30th March 2020) - Angulo, María Fernanda; Flores, Mauricio; Aranda, Mario; Henriquez-Aedo, Karem
Highlights: A new dansylation procedure was developed for biogenic amines detection. Dansylation reaction time was reduced in 88%. Chromatographic analysis time was reduced in 60%. The new procedure was successfully applied in beer and wine samples. Abstract: A new approach for biogenic amines (BA) determination in fermented beverages was developed coupling ultrafast dansylation conditions with ultra-high-performance liquid chromatography (UHPLC) method. Derivatization conditions for 8 amines analysis were optimized using D -optimal and central composite designs reducing in 88% the reaction time. Dansylated amines were separated on C18 column using a mobile phase composed of ammonium formate buffer and acetonitrile. Detection was performed by UV and fluorescence. Migration from conventional HPLC to UHPLC allowed a 60% reduction in analysis. The developed method was validated following ICH recommendations. Calibration data fitted a linear regression model with R 2 were values highest to 0.984. Repeatability and intermediate precision in matrix showed relative standard deviation (RSD) values lower than 4.86 and 11.53%, respectively. Detection and quantification limits ranged from 0.03 to 0.18 and from 0.20 to 0.59 mg mg L −1 . BA content in beer and wine samples were 10.53 to 73.17 mg L −1.